Triste animal metaphysicum. Tecnica, antropotecnica e nostalgia dell’ente - Simoncini, Francesco (Mechane, 2022)
When the problem of metaphysics is accessed through the horizon opened by modern technology, the question about the anthropological status of the human being becomes crucial. Attempt of this paper is then to conceive together the modern transition from technique to anthropotechnics and from technique to metaphysics as a nostalgia for being. Thus, the parallel anthropological characters of cunning (which as a long-term mechane renders man capable of Bildung) and hypocrisy (whereby the triste animal metaphysicum longs for the unity of the being he has first annihilated through technique) are brought to light.